Public Partisipation on Recruitmen System of Constitutional Judges - Sayyidatun Nashuha Basyar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The recruitment of constitutional judges is carried out by three state institutions, House of Representatives, Supreme Court, and President. Each of the three state institutions selects 3 (three) candidates for constitutional judges. In practice, there are differences in the system of recruitment of constitutional judges from the three state institutions, even differences in the system in one state institution with the same election period also occur in each state institution. There is a recruitment that does not meet transparency and participation as stated in Article 19 of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court which states that the nomination of constitutional judges must be transparent and participatory. The need for public participation in the system of recruitment of constitutional judges as a real benchmark in the integrity and capacity of constitutional judges so that it can foster more trust in the public in the Constitutional Court as the vanguard of the guardian of the constitution. This study uses normative legal research where the procedure for finding the truth. Thus, the importance of public participation in the recruitment of constitutional judges will be obtained.